2004
DOI: 10.1038/sj.onc.1208359
|View full text |Cite
|
Sign up to set email alerts
|

FGF2-induced upregulation of DNA polymerase-δ p12 subunit in endothelial cells

Abstract: p12 represents the smallest, so far poorly characterized subunit of the mammalian DNA polymerase d (pold) heterotetramer. Previously, to gain a molecular understanding of endothelial cell activation by fibroblast growth factor-2 (FGF2), we identified an upregulated transcript in FGF2-overexpressing murine aortic endothelial cells (FGF2-T-MAE cells) showing 89% identity with human p12. Here, we cloned the open reading frame of the murine p12 cDNA and confirmed the capacity of overexpressed or exogenously added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Our findings suggest that PDIP38 may possess functions in the mitochondria that may not be related to its ability to associate with pol ␦ and PCNA. In this regard, P12, the fourth subunit of pol ␦, was recently suggested to possess additional, cell proliferation-unrelated functions (61). Our results raise the possibility that PDIP38 may have functions that include interaction with the nuclear DNA replication system or in the linkage between pol ␦ and viral DNA replication.…”
Section: Discussionmentioning
confidence: 64%
“…Our findings suggest that PDIP38 may possess functions in the mitochondria that may not be related to its ability to associate with pol ␦ and PCNA. In this regard, P12, the fourth subunit of pol ␦, was recently suggested to possess additional, cell proliferation-unrelated functions (61). Our results raise the possibility that PDIP38 may have functions that include interaction with the nuclear DNA replication system or in the linkage between pol ␦ and viral DNA replication.…”
Section: Discussionmentioning
confidence: 64%
“…Although it is tempting to consider that p12 depletion may be involved in the inhibition of DNA synthesis that is observed after DNA damage with UV (see below), this may be too simplistic an explanation. It has been reported that p12 silencing in mouse endothelial cells causes a significant decrease in FGF2 (fibroblast growth factor)-stimulated cell growth (48). In these cells, p12 expression is specifically up-regulated by FGF2 but not by other mitogenic stimuli (48).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that p12 silencing in mouse endothelial cells causes a significant decrease in FGF2 (fibroblast growth factor)-stimulated cell growth (48). In these cells, p12 expression is specifically up-regulated by FGF2 but not by other mitogenic stimuli (48). Although the findings that p12 levels can affect cell proliferation are consistent with the hypothesis that this is due to effects on DNA synthesis via the modification of Pol ␦, a defect in Pol ␦ The ability of Pol ␦ 3-p12 to perform processive DNA synthesis was examined by its ability to extend a single primer on M13 DNA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the POLD4 ortholog of Cdm1 in Schizosaccharomyces pombe (S. pombe) is a nonessential gene (20), although it may be required in mammalian cells (21,22). To study human POLD4 functions, we depleted POLD4 using siD4 and analyzed the cell cycle progression.…”
Section: Pold4 Required For Cell Cycle Progressionmentioning
confidence: 99%